Determination of trace elements in undiluted wine samples using an automatized total sample consumption system coupled to ICP-MS. Issue 4 (4th January 2019) - Cerutti, Claudia; Sánchez, Carlos; Sánchez, Raquel; Ardini, Francisco; Grotti, Marco; Todolí, José-Luis
Abstract : A novel method for the elemental analysis of undiluted wine samples was optimized and validated. Abstract : A novel method for the elemental analysis of undiluted wine samples was optimized and validated. The method was based on the use of a high-temperature torch integrated sample introduction system (hTISIS) coupled to inductively coupled plasma mass spectrometry (ICP-MS). The operating conditions (hTISIS temperature and liquid flow rate) were optimized in terms of sensitivity and matrix effects. Low liquid flow rates allowed continuous introduction of organic samples into the plasma source with minimum soot as well as salt deposit formation at the ICP-MS interface and/or plasma thermal degradation. A double pass Scott-type spray chamber thermostated at 2 °C was taken as the reference sample introduction system. The results indicated that the hTISIS operated at 125 °C and a liquid flow rate of 30 µL min −1 improved the sensitivity and mitigated the extent of matrix effects compared to the conventional system. Once the optimum conditions were selected, the method was validated and applied to the determination of sixteen trace elements (Ti, V, Cr, Mn, Fe, Ni, Cu, Zn, As, Mo, Cd, Nd, Sm, Gd, Tb and Pb) in ten real wine samples. The sample was merely aspirated to the nebulizer with no additional preparation. For the sake of comparison, the samples were microwave digested and analyzed using a conventional setup. Method detection limits achieved by the hTISIS were 2 to 40 times lower than those found using the standard procedure and ranged from 0.002 to 6 µg kg −1 . Furthermore, the accuracy of the quantification using the hTISIS was not significantly different as compared to that afforded by the conventional procedure and substantially improved in comparison with the direct analysis of wine using a Scott spray chamber. The sample throughput was close to 10 h −1, which was in clear contrast with 2 h −1, estimated when the digestion method was used. Finally, the suitability of the developed method for the routine analysis of wine samples was demonstrated by performing a 20 hour long analysis sequence. Good signal stability and accurate results were obtained for ten representative Italian and Spanish wines.